2008
DOI: 10.1136/ard.2008.097642
|View full text |Cite
|
Sign up to set email alerts
|

STAT4 associates with systemic lupus erythematosus through two independent effects that correlate with gene expression and act additively with IRF5 to increase risk

Abstract: Objectives To confirm and define the genetic association of STAT4 and systemic lupus erythematosus, investigate the possibility of correlations with differential splicing and/or expression levels, and genetic interaction with IRF5. Methods 30 tag SNPs were genotyped in an independent set of Spanish cases and controls. SNPs surviving correction for multiple tests were genotyped in 5 new sets of cases and controls for replication. STAT4 cDNA was analyzed by 5’-RACE PCR and sequencing. Expression levels were me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
109
1
2

Year Published

2009
2009
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 142 publications
(117 citation statements)
references
References 29 publications
5
109
1
2
Order By: Relevance
“…We found no significant association of any genotype with mRNA levels of STAT4a and STA4b among 30 pSS patients. A lack of power does not likely explain the discrepancies between our results and those from Abelson et al 8 because no trend effect was observed. We wondered whether the functional consequences of STAT4 risk allele might be explained by an environmental upregulation of STAT4 among pSS patients.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…We found no significant association of any genotype with mRNA levels of STAT4a and STA4b among 30 pSS patients. A lack of power does not likely explain the discrepancies between our results and those from Abelson et al 8 because no trend effect was observed. We wondered whether the functional consequences of STAT4 risk allele might be explained by an environmental upregulation of STAT4 among pSS patients.…”
Section: Discussioncontrasting
confidence: 99%
“…Moreover, the significant association of both STAT4 and IRF5 polymorphisms has been also reported for other autoimmune diseases or inflammatory conditions, such as systemic sclerosis, 14 rheumatoid arthritis, 15 lupus. 8,11,[15][16][17][18] Interestingly, all these autoimmune diseases could be, to some extent type 1 IFN driven. This study provides additional data suggesting that STAT4 and IRF5 function independently on pSS genetic susceptibility, with an additive effect but with no epistatic interaction between both genes, which confirms the findings from Nordmark et al 6 in patients of North European ancestry.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, gene polymorphisms at the interferon regulatory factor 5 (IRF5), a major mediator of TLR-triggered expression of type I IFN [53] and other proinflammatory cytokines, including TNFa [54], act additively with STAT4 genotype to increase the risk for SLE [13,55]. This fact could be explained by the functional link between both molecules, since the risk allele of STAT4 determines a higher frequency of anti-dsDNA antibodies in SLE patients, allowing a continued type I IFN stimulation of the STAT4-dependent autoimmune response [13,53].…”
Section: Discussionmentioning
confidence: 99%